Strategic Management as a Concept of Survival in Particular Environment : Case Study of the hotel Residence Spalena - Grishaeva, Elina (2018)
This Bachelor thesis is addressing the topic of usage of the strategic management in different environmental conditions. The aim of the thesis is to critically assess the current state of the hotel Residence Spalena, identify crisis situations and provide recommendations for future improvements based on the concept of strategic management. For the research purposes both primary and secondary data are used. The author used qualitative and quantitative methods of data collection, such as interviews with management and staff of the company and evaluation of the collected statistics. The result was a number of recommendations to promote the efforts of company management in crisis situations for hotel Residence Spalena.